Level of service for assessing streets and public spaces: the case of hsistorical Aleppo - N. V. Danilina; L. Alibrahim (Vestnik MGSU)
Introduction. Historic cities face the issues of sustainable development, especially city centres that have high cultural value. One of the most important topics is ensuring connectivity and accessibility as road and street networks in historic centres have their own characteristics: narrow alleys, high density of buildings, vehicles, pedestrian flows and a variety of public activities. In this aspect, there is the research interest to assess current condition of streets in the historic centres to make informed decisions about their reconstruction in order to create a flexible, comfortable and safe public environment.Materials and methods. Selecting Aleppo city as the object of study, analyzing the current situation of general plan and infrastructure of the city using GIS maps, open public data and information provided by local municipality of the city and through applying (LOS-Level of Service) method which is designed for analyzing transportation networks in this case in the historic city centre.Results. A classification of the streets of the historic city centre was developed, which is designed due to pedestrian ratios, taking into account hierarchy that considers the valuable heritage objects that are located near the studied streets that attract visitors. As a final result a method was suggested for the purpose of ranking level of street services from A to F and the classification of streets according to their values.Conclusions. Identified streets that require reconstruction solutions to improve the quality of the urban environment, with the aim of creating comfortable and safe conditions for pedestrians, while ensuring the accessibility of the urban infrastructure, taking into account its historical value.